HUBUNGAN POLA ISTIRAHAT, STRESS, DENGAN TERJADINYA GANGGUAN SIKLUS MENSTRUASI (OLIGOMENOREA) PADA WANITA USIA SUBUR (WUS) DI TLOGO WULAN, KEL. TLOGOMAS, KEC. LOWOKWARU, KOTA MALANG - Kuswandari, Eti; Ningrum, Novi Budi; Rahmawati, Mufida Annisa; Ummah, Wiqodatul; Aisyah, Fitria (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Oligomenorrhea is a condition in which the menstrual cycle extends for more than 35 days. This condition refers to the normal menstrual cycle shifting to more than 35 days. Or women who have fewer than nine menstrual periods in a year. The purpose of this study was to determine the relationship between rest patterns, stress and the occurrence of menstrual cycle disorders (oligomenorrhea) in women of childbearing age in Tlogo Wulan, Tlogomas Village, Lowokwaru District, Malang City.The research method used in this study is a quantitative method because the research data are numbers and analysis using statistics. This research was conducted in Tlogo Wulan, Kel. Tlogomas, Kec. Lowokwaru, Malang City from August to October 2021. The independent variables in this study are Rest Patterns (X1) and Stress (X2), the dependent variable is Oligomenorrhea (Y). Sampling uses a random sampling technique, namely sampling based on certain considerations such as population characteristics or previously known characteristics. Data collection is done in the form of interviews, documentation, and questionnaires designed by researchers based on theory.The t-count value of the resting pattern variable (X1) is 8,210 > ttable 2,020, meaning that there is a significant relationship between the resting pattern (X1) and the occurrence of oligomenorrhea (Y). The tcount value of the stress variable (X2) is 2,066 > ttable 2,020, meaning that there is a significant relationship between stress (X2) and the occurrence of oligomenorrhea (Y). The Fcount value of 53,545 > from the F0.05 (3,23) value means that there is a significant simultaneous or simultaneous relationship between the rest pattern variable (X1), stress (X2), and the occurrence of oligomenorrhea (Y). The value of the regression coefficient (Rsquare) of 0,723 means that the relationship between the independent variables and the incidence of oligomenorrhea is 72,3%, while the other 27,7% is influenced by other factors not examined. Judging from the relationship of the two independent variables (X) to the dependent variable (Y) it can be concluded that the resting pattern variable (X1) is more dominant in the incidence of oligomenorrhea (Y) as evidenced by the tcount 8,210 > ttable 2,020.